Pembuatan dan Pengujian Pupuk Organik Cair (POC) dari Limbah Pasar dengan Menggunakan Bioaktivator EM4 - Delinda Nirmala Afiyah; Emelia Uthari; Dewi Widyabudiningsih; Retno Dwi Jayanti (Jurnal Kimia Fullerene, 2021)
Organic waste from market rubbish can be utilized as liquid organic fertilizer. In general, liquid organic fertilizers contain nutrients such as Nitrogen, Phosphorus, Potassium, and C-Organic that are needed by plants. The objective of this research are to manufacture liquid organic fertilizer through anaerobic fermentation from market rubbish with the addition of an EM4 bio activator and to determine the optimum time. The nutrients content were determined using the Kjeldahl method, UV-VIS Spectrophotometry, and Atomic Adsorption Spectroscopy. Liquid Organic Fertilizer that had the best quality among all types is from non-green vegetable. It has 0,45% of nitrogen, 0,08% of phosphorus, 0,34% of potassium, and 2,8% of C-organic respectively. The optimum time for POC fermentation occurred on the 14th day. The nutrient levels of all types of liquid organic ferilizer produced have not meet the minimum technical requirements of the quality of liquid organic fertilizers based on the Decree of the Minister of Agriculture of the Republic of Indonesia Number 261/Kpts/Sr.310/M/4/2019